An Assessment of Property Tax Administration in Edo State, Nigeria - Toju Francis Balogun (Indonesian Journal of Geography, 2019)
ABSTRACTThe mode of administration of property tax determines its buoyancy. The study utilizes key informant method to examine the mode of operation of Edo State Land Use Charge.  The study observes that property tax revenue mobilization in Benin Metropolis is ineffective due to unsystematic tax administration procedure employed by Land Use Charge Department. The study shows that inadequate personnel, public contempt, limited coverage of the tax base and shrouded valuation method are major problems of the Land Use Charge in Benin metropolis. It also reveals that the current property tax administration will not appreciably enhance the internally generated revenue except the mode of operation is reformed. To overcome these challenges it is recommended among others that the implementation of modern and transparent assessment methods for real estate utilizing remote sensing and GIS integrated with computer-assisted mass appraisal (CAMA) be incorporated through a public-involved debate on property tax reform. Modus administrasi pajak properti menentukan daya apung. Penelitian ini menggunakan metode informan kunci untuk memeriksa modus operasi dari Edo Negara Penggunaan Tanah Charge. Penelitian ini mengamati bahwa pajak properti mobilisasi pendapatan di Benin Metropolis tidak efektif karena prosedur administrasi perpajakan sistematis dipekerjakan oleh Penggunaan Tanah Mengisi Department. Studi ini menunjukkan bahwa personil yang tidak memadai, penghinaan publik, cakupan terbatas basis pajak dan metode penilaian diselimuti masalah utama dari Penggunaan Tanah Mengisi di Benin metropolis. Ia juga mengungkapkan bahwa administrasi pajak properti saat ini tidak akan lumayan meningkatkan pendapatan yang dihasilkan secara internal kecuali modus operasi direformasi. Untuk mengatasi tantangan ini dianjurkan antara lain bahwa pelaksanaan metode penilaian modern dan transparan untuk real estate memanfaatkan penginderaan jauh dan GIS terintegrasi dengan komputer-dibantu penilaian massa (CAMA) dimasukkan melalui debat publik-terlibat pada reformasi pajak properti.